Porcine Epidemic Diarrhoea Virus in Italy: Disease spread and the role of transportation. Issue 6 (9th August 2018) - Boniotti, Maria Beatrice; Papetti, Alice; Bertasio, Cristina; Giacomini, Enrico; Lazzaro, Massimiliano; Cerioli, Monica; Faccini, Silvia; Bonilauri, Paolo; Vezzoli, Fausto; Lavazza, Antonio; Alborali, Giovanni Loris
Abstract: Porcine Epidemic Diarrhoea Virus (PEDV) causes watery diarrhoea, dehydration, and a high mortality rate among suckling pigs. Recently, PEDV had a large negative economic impact on the swine industries in Asia and North America. In 2014, PEDV re‐emerged in many European countries, but most countries only reported a few sporadic cases. Here, we report the epidemic wave that occurred in Italy from 2015 to 2017. During this time, PEDV was detected by real‐time PCR in 438 farms located mainly in the high‐density pig production area in Northern Italy. Most of the outbreaks were in farrow‐to‐finish, farrow‐to‐wean and finisher farms. Clinical signs were observed mainly in suckling and fattening animals, while mortality rates were higher in piglets, reaching 50%. A sequence analysis showed that a PEDV strain, similar to the OH851 S‐INDEL strain isolated in the USA in January 2014, was responsible for the outbreaks in Italy in 2015 and 2016. However, from January 2017, a recombinant variant strain, containing a portion of the Swine Enteric Coronavirus in the S1 gene, spread and almost completely outcompeted the previous nonrecombinant strain. In total, 14.1% of the environmental swabs collected from trucks at slaughterhouses after animals were unloaded tested positive for PEDV before the trucks were cleaned and disinfected, and 46% remained positive after cleaning and disinfection processes were performed. Moreover, environmental swabs indicated that 17.3% of the empty trucks arriving at the farms to load animals were PEDV‐positive. This study indicates that trucks can have an important role in the spread of PEDV in Italy.